Implantable Ventricular Assist Device Use and Outcomes in People With End‐Stage Renal Disease - Walther, Carl P. (J Am Heart Assoc, 2018)
BACKGROUND: People with end‐stage renal disease (ESRD) are at risk for advanced heart failure, but little is known about use and outcomes of durable mechanical circulatory support in this setting. We examined use and outcomes of implantable ventricular assist devices (VADs) in a national ESRD cohort. METHODS AND RESULTS: We performed a retrospective cohort study of Medicare beneficiaries with ESRD who underwent implantable VAD placement from 2006 to 2014. We examined in‐hospital and 1‐year mortality, all‐cause and cause‐specific hospitalizations, and heart/kidney transplantation outcomes. We investigated as predictors demographic factors, time‐period of VAD implantation, primary or post‐cardiotomy implantation, and duration of ESRD before VAD implantation. We identified 96 people with ESRD who underwent implantable VAD placement. At time of VAD implantation, 74 (77.1%) were receiving hemodialysis, 10 (10.4%) were receiving peritoneal dialysis and 12 (12.5%) had renal transplant. Time from incident ESRD to VAD implantation was median 4.0 (interquartile range 1.1, 8.2) years. Mortality during the implantation hospitalization was 40.6%. Within 1 year of implantation 61.5% of people had died. On multivariable analysis, males had half the mortality risk of females. Lower mortality risk was also seen with VAD implantation in a primary setting, and with more recent year of implantation, but these results did not reach statistical significance. CONCLUSIONS: Medicare beneficiaries with ESRD are undergoing durable VAD implantation, often several years after incident ESRD, although in low numbers. Mortality is high among these patients, highlighting the need for investigations to improve treatment selection and management.